Adapting population health interventions for new contexts: qualitative interviews understanding the experiences, practices and challenges of researchers, funders and journal editors. Issue 10 (26th October 2022) - Copeland, Lauren; Littlecott, Hannah J; Couturiaux, Danielle; Hoddinott, Pat; Segrott, Jeremy; Murphy, Simon; Moore, Graham; Evans, Rhiannon E
Abstract : Objectives: Research on the adaptation of population health interventions for implementation in new contexts is rapidly expanding. This has been accompanied by a recent increase in the number of frameworks and guidance to support adaptation processes. Nevertheless, there remains limited exploration of the real-world experiences of undertaking intervention adaptation, notably the challenges encountered by different groups of stakeholders, and how these are managed. Understanding experiences is imperative in ensuring that guidance to support adaptation has practical utility. This qualitative study examines researcher and stakeholder experiences of funding, conducting and reporting adaptation research. Setting: Adaptation studies. Participants: Participants/cases were purposefully sampled to represent a range of adapted interventions, types of evaluations, expertise and countries. Semistructured interviews were conducted with a sample of researchers (n=23), representatives from research funding panels (n=6), journal editors (n=5) and practitioners (n=3). Measures: A case study research design was used. Data were analysed using the framework approach. Overarching themes were discussed within the study team, with further iterative refinement of subthemes. Results: The results generated four central themes. The first three relate to the experience of intervention adaptation (1) involving stakeholders throughout the adaptation process and how to integrate the evidence base with experience; (2) selecting the intervention and negotiating the mismatch between the original and the new context; and (3) the complexity and uncertainty when deciding the re-evaluation process. The final theme (4) reflects on participants' experiences of using adaptation frameworks in practice, considering recommendations for future guidance development and refinement. Conclusion: This study highlights the range of complexities and challenges experienced in funding, conducting and reporting research on intervention adaptation. Moving forward, guidance can be helpful in systematising processes, provided that it remains responsive to local contexts and encourage innovative practice.